2013
DOI: 10.1073/pnas.1305624110
|View full text |Cite
|
Sign up to set email alerts
|

Uracil in duplex DNA is a substrate for the nucleotide incision repair pathway in human cells

Abstract: Spontaneous hydrolytic deamination of cytosine to uracil (U) in DNA is a constant source of genome instability in cells. This mutagenic process is greatly enhanced at high temperatures and in single-stranded DNA. If not repaired, these uracil residues give rise to C→T transitions, which are the most common spontaneous mutations occurring in living organisms and are frequently found in human tumors. In the majority of species, uracil residues are removed from DNA by specific uracil-DNA glycosylases in the base … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 46 publications
4
40
0
1
Order By: Relevance
“…Therefore, in ung −/− ape2 Y/− GC B cells, which have SMUG1 and only very low levels of APE1, this pathway would be very inefficient at generating SSBs that can lead to mutations at A:T bp. Alternatively, or in addition, our data are consistent with the possibility that APE2 might incise the DNA backbone at dU bases, in addition to AP sites, consistent with a recent report (54). Although APEs are thought to act specifically at AP sites, this study showed that APE1 can incise DNA at dU in duplex DNA, albeit inefficiently.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, in ung −/− ape2 Y/− GC B cells, which have SMUG1 and only very low levels of APE1, this pathway would be very inefficient at generating SSBs that can lead to mutations at A:T bp. Alternatively, or in addition, our data are consistent with the possibility that APE2 might incise the DNA backbone at dU bases, in addition to AP sites, consistent with a recent report (54). Although APEs are thought to act specifically at AP sites, this study showed that APE1 can incise DNA at dU in duplex DNA, albeit inefficiently.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, the fate of U:G appears to be more complex because SMUG1 and TDG have been suggested to contribute to repair in addition to UNG1/2, at least in cell-free extracts (5,14). Moreover, alternative to a canonical BER, this lesion can undergo a direct incision by human APE1 (26) and may also be coprocessed by the mismatch repair if a nick or another uracil are present simultaneously in DNA (35). In our substrates containing a unique uracil, it was certainly not the mismatch repair activity that caused the inhibition of transcription (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This result confirms that UNG1/2 contributes to U:G excision but also indicates a significant input of another uracil-DNA glycosylase (or other glycosylases). Alternatively, the removal of uracil might take place by a recently described mechanism initiated directly by APE1 (26).…”
Section: Incision At Uracil Opposite a Guanine By Cell-free Extracts mentioning
confidence: 99%
“…It has been suggested that the NIR pathway can serve as a backup system for BER if the appropriate glycosylase is missing or inefficient. Once the AP endonuclease has produced the initial incision, the full regeneration and repair of the incised strand can occur as long as the other, subsequent repair factors are also available [18]…”
Section: Mechanisms Of Dna Repairmentioning
confidence: 99%